Adjunctive treatment with ticagrelor, but not clopidogrel, added to tPA enables sustained coronary artery recanalisation with recovery of myocardium perfusion in a canine coronary thrombosis model - Wang, Kai; Zhou, Xiaorong; Huang, Yanming; Khalil, Mazen; Wiktor, Dominik; van Giezen, J. J. J.; Penn, Marc S. (Thrombosis and Haemostasis, 2010)
Reperfusion therapy for myocardial infarction is limited by significant re-occlusion rates and less-than-optimal myocardial tissue perfusion. It was the objective of this study to assess and compare the effect of ticagrelor, the first reversibly binding oral P2Y12 receptor antagonist, with that of clopidogrel, in conjunction with thrombolytic therapy, on platelet aggregation, thrombus formation, and myocardial perfusion in a canine model. Thrombus formation was induced by electrolytic injury and blood flow was measured with a Doppler ultrasonic flowmeter. All animals received tissue plasminogen activator (tPA) (1 mg/kg over 20 min); 10 animals received clopidogrel (10 mg/kg IV bolus over 5 min), 10 animals received ticagrelor initiated with a 1-min bolus (75 μg/kg/ min), followed by continuous infusion (10 μg/kg/min) for 2 h, and 10 animals received IV saline. Re-occlusion rate and cyclic flow variation decreased with ticagrelor compared to saline groups (p<0.05). Adenosine phosphate (ADP)-induced platelet aggregation decreased with ticagrelor (1.9% ± 2.67) and clopidogrel (1.11% ± 2.0) vs. saline (26.3% ± 23.5, p<0.05) at the end of adjunctive therapy. Bleeding time increased in the clopidogrel compared to the ticagrelor group (p=0.01). Infarct size was reduced with ticagrelor compared to the clopidogrel and saline groups (p<0.05). Blood flow remained significantly below baseline values at 20 min after tPA administration in the saline and clopidogrel groups but not in the ticagrelor group. In conclusion, in a dog coronary thrombosis model, ticagrelor blocks ADP-induced platelet activation and aggregation; prevents platelet-mediated thrombosis; prolongs reperfusion time and reduces re-occlusion and cyclic flow variation; and significantly decreases infarct size and rapidly restores myocardial tissue perfusion.
Keywords: P2Y12 receptor; thrombosis; myocardial tissue perfusion; myocardial contrast echocardiography; ticagrelor